SNAP-25 Contributes to Neuropathic Pain by Regulation of VGLuT2 Expression in Rats. (15th December 2019) - Wang, Jiang; Xu, Wei; Kong, Yan; Huang, Jiangju; Ding, Zhuofeng; Deng, Meiling; Guo, Qulian; Zou, Wangyuan
Highlights: Cleavage of SNAP-25 reduced VGluT2 expression in rats with neuropathic pain. Overexpression of SNAP-25 increased VGluT2 expression and induced allodynia in rats. BoNT/A inhibited astrocyte activation, upregulation of VGluT2 abolished this effect. PKA/p-CREB pathway was involved in SNAP-25-mediated regulation of neuropathic pain. Abstract: Synaptosomal-associated protein 25 (SNAP-25) plays an important role in neuropathic pain. However, the underlying mechanism is largely unknown. Vesicular glutamate transporter 2 (VGluT2) is an isoform of vesicular glutamate transporters that controls the storage and release of glutamate. In the present study, we found the expression levels of VGluT2 correlated with the upregulation of SNAP-25 in the spinal cord of rats following chronic constriction injury (CCI)-induced neuropathic pain. Cleavage of SNAP-25 by Botulinum toxin A (BoNT/A) attenuated mechanical allodynia, downregulated the expression of VGluT2 and reduced glutamate release. Overexpression of VGluT2 abolished the antinociceptive effect of BoNT/A. Upregulation of SNAP-25 in naive rats increased VGluT2 expression and induced pain-responsive behaviors. In pheochromocytoma (PC12) cells, the expression of VGluT2 was also depended on SNAP-25 dysregulation. Moreover, we found VGluT2 was involved in SNAP-25-mediated regulation of astrocyte expression and activation of the PKA/p-CREB pathway mediated the upregulation of SNAP-25 in neuropathic pain. The findings of our study indicate that VGluT2 contributes to the effect of SNAP-25 in maintaining the development of neuropathic pain and suggests a novel mechanism underlying SNAP-25 regulation of neuropathic pain.